2010
DOI: 10.1002/jctb.2418
|View full text |Cite
|
Sign up to set email alerts
|

Limestone dissolution in flue gas desulfurization—experimental and numerical study

Abstract: BACKGROUND: Wet FGD technologies account for around 87% of such systems worldwide, particularly those that use limestone as the absorbent. This technique is widely used in large thermal power stations. Limestone reactivity is one of the parameters that most influence the yield of the FGD process. With the aim of improving the design and operation of desulfurization units, many studies have been carried out to investigate the rate of limestone dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…For this reason, Flue Gas Desulfurization, FGD, plays a key role when coal-fired power plants are utilized. In fact, almost 90% of the FGD units is constituted by wet FGD, WFGD, scrubbers [6]. Therefore, improvements proposed to this technology, like in the case of this article, would represent an advance of primary importance to reduce pollution and energy consumption.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For this reason, Flue Gas Desulfurization, FGD, plays a key role when coal-fired power plants are utilized. In fact, almost 90% of the FGD units is constituted by wet FGD, WFGD, scrubbers [6]. Therefore, improvements proposed to this technology, like in the case of this article, would represent an advance of primary importance to reduce pollution and energy consumption.…”
Section: Introductionmentioning
confidence: 94%
“…Figure 12 demonstrates a comparison between the fitting of experimental data provided by Equation (6) It can be noticed that Equation (2) is not suitable to describe the limestone dissolution in the presence of ultrasound and this is not exclusively valid for second order reaction, but also for other diverse orders. Equation (6) would suggest that ultrasonic power contributes to diverse phenomena involved in the dissolution of the solid particles. These phenomena are not only related to the breakage of the particles but they could also influence their reactivity.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…A wide variety of methods for sulfur dioxide abatement are found in industry; out of these, wet flue gas desulfurization (WFGD) has been regarded as one of the most widely applied methods . It has been reported that approximately 87% of the worldwide industrial emissions of SO 2 are controlled by means of WFGD scrubbers . This technology has proven successful mainly due to its high removal efficiency, which can be up to 95% or higher, the low cost of the reagent (mainly limestone), and the production of gypsum with a potential market value .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the improvements in power efficiency within WFGD technologies are motivated when considering that the amount of power required for reducing SO 2 emissions worldwide (or at least in the OECD) is approximately equal to the power required by a country to provide electricity for residential purposes, including heating. It has been reported previously that one of the rate determining parameters of the SO 2 absorption process is limestone dissolution. , Moreover, the limestone dissolution rate has been considered to be an important design factor of WFGD scrubbers since it affects the slurry alkalinity, the residence time in the lower section of the absorber, and the SO 2 mass transfer rate . Limestone dissolution has been previously studied for a wide variety of topics including acid water remediation, carbonate geological behavior, or oil well acid-rock interaction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation